2004
DOI: 10.4049/jimmunol.172.7.4091
|View full text |Cite
|
Sign up to set email alerts
|

Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase Substrate 1 Regulates the Migration of Langerhans Cells from the Epidermis to Draining Lymph Nodes

Abstract: Src homology 2 domain-containing protein tyrosine phosphatase substrate 1 (SHPS-1) is a member of the signal regulatory protein family in which the extracellular region interacts with its ligand, CD47. Recent studies have demonstrated that SHPS-1 plays an important role in cell migration and cell adhesion. We demonstrate in this study, using immunohistochemical and flow cytometric analyses, that murine Langerhans cells (LCs) express SHPS-1. Treatment of mice ears with 2,4-dinitro-1-fluorobenzene significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 54 publications
4
60
0
Order By: Relevance
“…This is further supported by the observation that the TNF-a-induced up-regulation of I-A expression by LC is attenuated by the ligation of SHPS-1, because it has been reported that TNF-a induces both the maturation of DC and the phosphorylation of tyrosine residues of SHPS-1 and the consequent recruitment of 17]. We previously reported that the motility of LC is attenuated in wild-type mice by the engagement of SHPS-1 and in SHPS-1 mutant mice [32]. As immature DC, following induction of maturation after stimulation by inflammatory cytokines or haptens, up-regulate CCR7 [39,41,42], our next question was whether or not the expression of CCR7 on LC is impaired during the maturational changes following hapten application to SHPS-1 mutant mice.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This is further supported by the observation that the TNF-a-induced up-regulation of I-A expression by LC is attenuated by the ligation of SHPS-1, because it has been reported that TNF-a induces both the maturation of DC and the phosphorylation of tyrosine residues of SHPS-1 and the consequent recruitment of 17]. We previously reported that the motility of LC is attenuated in wild-type mice by the engagement of SHPS-1 and in SHPS-1 mutant mice [32]. As immature DC, following induction of maturation after stimulation by inflammatory cytokines or haptens, up-regulate CCR7 [39,41,42], our next question was whether or not the expression of CCR7 on LC is impaired during the maturational changes following hapten application to SHPS-1 mutant mice.…”
Section: Discussionmentioning
confidence: 90%
“…Murine epidermal sheets were prepared as previously described [32]. After fixation, the sheets were simultaneously incubated at room temperature for 30 min with FITCconjugated mouse anti-mouse I-A b mAb and PE-conjugated rat anti-mouse CD86 mAb, each diluted 1:100 in 5% BSA/PBS.…”
Section: Preparation Of Murine Epidermal Sheets and Immunofluorescencmentioning
confidence: 99%
See 3 more Smart Citations